Proposisi Kewargaan Dalam Islam: Tafsir Baru Konsep Ummah - Abdul Fattah (Universitas Islam Negeri Mataram, 2005)
An Islamic term relating to discourse of citizenship is ummah. In Islamic terminology, the term is a unique one, and no other equal term of Western languages that has the same range of meaning as it does. While other terms—e.g. the people, the nation, or the state—are respectively limited under certain culture, ethnic, race, geography, language, historical element shared or combination of them all, the term of ummah goes beyond these all borders of meaning. This article is aimed at revealing the range meaning of the term ummah and reformulating it in the current modern context. The term is stated in the Qur’an 64 times in 24 different chapters, surah, through two expressions of meaning. First, it is used in homonym with several meaning like certain time, model, animals, related to term ummî, or genie. Secondly, it is used in terms of unification of religious community with its all branches. As comparison, in the Madinah Carter the term is used in two senses of meaning. First, in the article 1, with likely exclusive sense, it is used to mean an organization or community that shares a same religion. Secondly, in the article 25, with more inclusive sense, it is used to mean a pluralistic community that share or live in a socio-politic unity. The two kind of using the term ummah in the Qur’an and the Madinah Carter indicate that Islam has given clear identity to the concept of ummah, and taught a spirit of universality that is bundled by the spirit of shared faith brotherhood. The concept goes beyond the limitation of ethnicity, race, group, language, and territorial border, as what is going on in the Western knowledge and practices.